PSYCHOLOGICAL CONDITIONS OF DEVELOPMENT OF STRESS TOLERANCE OF THE PERSONALITY IN ADULTHOOD - Тептюк, Ю. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The psychological features and development factors which are the psychological conditions of stress tolerance development in person’s adulthood, are revealed In the article. A feature of the stress tolerance development in person’s adulthood implies that adulthood is the most stress-resistant age period, because an adult, by analyzing its own experience, is able to develop certain personal qualities that contribute to the development of this important feature. It is stated that the main personal factors that affect the level of resistance to stress, are properties of the nervous system and temperament, anxiety, self-esteem, locus of control, optimistic or pessimistic styles of thinking, attitudes, values and motivation to succeed, the degree of conflict and moral normativity. Key words: psychological conditions, stress, adulthood, own experience, personality qualities.